Uncovering Gen Z Indonesia's Impulse Shopping Behaviour on E- Commerce Tiktok Shop (The Manager Review, 2025)
This study aims to investigate how impulse buying is influenced by time pressure, live shopping and emotional intelligence, and to examine the role of perceived value as a mediator. The purposive sampling technique was applied to a total of 450 Generation Z consumers on TikTok Shop Indonesia as respondents who had made or were making purchases through live shopping. Data processing was conducted using SEM-PLS. The results of the structural equation modeling indicate that by time pressure, live shopping, emotional intellegence and perceived value have a positive and significant effect on impulse buying. Time pressure, live shopping and emotional intelligence also have a positive and significant impact on impulse buying. Furthermore, perceived value was found to positively and significantly mediate the relationship between time pressure, live shopping and emotional intelligence with impulse buying, exhibiting complementary partial mediation. This study explores the influence of time pressure, live shopping and emotional intelligence on impulse buying, mediated by perceived value, in the context of consument TikTok Shop on Indonesia. Future research should consider contextual factors that may influence the relationships identified in this study.